2004
DOI: 10.1023/b:cohc.0000028632.61226.cd
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of 3,4-Dihydropyrrolo[1,2-a]pyrazines

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In previous work [6], we showed that dipyrrolo[1,2-a:2',1'-c]pyrazines form ditrifluoroacetyl derivatives as the major reaction products with excess trifluoroacetic anhydride even at room temperature. On the other hand, much more complicated behavior is found for 3,4-dihydropyrrolo[1,2-a]pyrazines, for which the direction of the reaction depends on the structure of the starting compounds and substrate/reagent ratio [7].The α-position of the pyrrole ring in 1-methylpyrrolo[1,2-a]pyrazine (1) is unoccupied and we might expect that the most likely product in its reaction with trifluoroacetic anhydride would be 6-trifluoroacetylpyrrolo[1,2-a]pyrazine by analogy to acylation by acetic anhydride [1]. However, the reaction of 1 with a 2.5-fold excess of trifluoroacetic anhydride in benzene (method A) yielded three products.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work [6], we showed that dipyrrolo[1,2-a:2',1'-c]pyrazines form ditrifluoroacetyl derivatives as the major reaction products with excess trifluoroacetic anhydride even at room temperature. On the other hand, much more complicated behavior is found for 3,4-dihydropyrrolo[1,2-a]pyrazines, for which the direction of the reaction depends on the structure of the starting compounds and substrate/reagent ratio [7].The α-position of the pyrrole ring in 1-methylpyrrolo[1,2-a]pyrazine (1) is unoccupied and we might expect that the most likely product in its reaction with trifluoroacetic anhydride would be 6-trifluoroacetylpyrrolo[1,2-a]pyrazine by analogy to acylation by acetic anhydride [1]. However, the reaction of 1 with a 2.5-fold excess of trifluoroacetic anhydride in benzene (method A) yielded three products.…”
mentioning
confidence: 99%
“…In previous work [6], we showed that dipyrrolo[1,2-a:2',1'-c]pyrazines form ditrifluoroacetyl derivatives as the major reaction products with excess trifluoroacetic anhydride even at room temperature. On the other hand, much more complicated behavior is found for 3,4-dihydropyrrolo[1,2-a]pyrazines, for which the direction of the reaction depends on the structure of the starting compounds and substrate/reagent ratio [7].…”
mentioning
confidence: 99%